Community Preferences and the Representative Consumer - Muellbauer, John (Econometrica, 1976)
[A representative consumer exists if market behavior corresponds to a representative income or utility level which is a function of the income distribution. Necessary and sufficient conditions are given on micro behavior and macro behavior (whether maximizing or not) for a representative consumer to exist. Nonlinear Engel curves and taste differences are permitted. If the representative income level is restricted to be mean income, we obtain the traditional linear Engel curves solution. A striking result on economy of information in the representation of a social welfare function is given.]